2015
DOI: 10.1177/1352458515590647
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid amounts of HLA-G in dimeric form are strongly associated to patients with MRI inactive multiple sclerosis

Abstract: Our findings suggest that HLA-G dimers may be implicated in termination of inflammatory response occurring in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The membrane was incubated with a HRP‐conjugated anti‐mouse antibody (1:5000; Amersham Biosciences, Piscataway, NJ, USA) and developed with the ECL kit (Amersham Biosciences). The images were acquired by Geliance 600 (Perkin Elmer, Massachusetts, USA) . 721.221G cell culture supernatants and HLA‐G‐negative sera were used as positive and negative controls, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane was incubated with a HRP‐conjugated anti‐mouse antibody (1:5000; Amersham Biosciences, Piscataway, NJ, USA) and developed with the ECL kit (Amersham Biosciences). The images were acquired by Geliance 600 (Perkin Elmer, Massachusetts, USA) . 721.221G cell culture supernatants and HLA‐G‐negative sera were used as positive and negative controls, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The images were acquired by Geliance 600 (Perkin Elmer, Massachusetts, USA). 13 721.221G cell culture supernatants and HLA-G-negative sera were used as positive and negative controls, respectively.…”
Section: Measurements Of Shla-g Concentrationsmentioning
confidence: 99%
“…Dimers of sHLA-G have been also analyzed by Fainardi et al in MS. They demonstrated that HLA-G dimers in cerebrospinal fluid were more frequent in MS patients than in controls and in magnetic resonance imaging (MRI) inactive than in MRI active MS patients, thus suggesting that HLA-G dimers may be implicated in termination of inflammatory response in MS [ 66 ]. Moreover, Mohammadi et al have observed that 14 bp insertion in HLA-G could result in lower plasma HLA-G levels in patients, and they found a significant correlation of HLA-G genotype and its plasma levels with MS susceptibility, thus suggesting a role for HLA-G as a risk factor for MS [ 67 ].…”
Section: Hla-g In Autoimmune/inflammatory Diseasesmentioning
confidence: 99%
“…Although HLA‐G heterodimers of different isoforms such as HLA‐G1‐HLA‐G5 or HLA‐G1‐HLA‐G2 have not been detected yet, such dimers might occur through the Cys42 of their α1 domains. SDS‐PAGE under nonreducing conditions are often used for identification of these high‐molecular weight HLA‐G dimers/HLA‐G monomers . Nevertheless, the exclusive usage of such strategies should be considered with caution for the qualitative and quantitative detection of dimers or monomers, as posttranslational modification also increases the size of HLA‐G molecules.…”
Section: Hla‐g Dimers and Oligomers: The Second Dimension Of The Strumentioning
confidence: 99%